You Can't Fix What You Don't Measure: How ALICE Can Help Rebuild the Middle Class. (26th July 2019) - Hoopes, Stephanie; Treglia, Dan
Abstract: Seventy percent of Americans identify as middle class, but one in three middle‐income households do not earn enough to support their family at the most basic level, and four in five do not earn enough to afford a sustainable budget. This incongruity explains the increasing frustration of many workers. Yet official government measures do not capture this reality, and as a result, policy makers continue to create economic policies that perpetuate the structural mismatch between wages and costs. This Viewpoint essay addresses these shortcomings. After reviewing alternatives to the federal poverty level, it argues that the most realistic and accurate floor to the middle class is the ALICE (Asset Limited, Income Constrained, Employed) Household Survival Budget. The essay then turns to policies that help realign wages and cost of living and presents initiatives that are being implemented in states across the country. Four policy areas would enable more workers to support their families and fulfill the promise of being middle class in America: meaningful work with stable and sufficient wages, upskilling and digital retooling, fiscal cushion for periods of financial instability, and affordable credit .